Factors Affecting Intradialytic Hypertension - Imam Hadi Yuwono; Anggorowati Anggorowati; Wahyu Hidayati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Intradialytic hypertension, defined as an increase in blood pressure during or immediately after hemodialysis which results in postdialysis hypertension, has long been recognized to complicate the hemodialysis procedure, yet it is often largely ignored. Intradialytic hypertension affects the quality of life of patients undergoing hemodialysis and reduces their survival and increases mortality in CKD patients on hemodialysis. Objective to identify other factors that influence the occurrence of intradialytic hypertension. We conducted a literature search through the ScienceDirect, Scopus, and PubMed databases. The keywords used are